Analisis Siyasah Tanfidziyyah terhadap Pengawasan Peratin dalam Pencegahan Penyimpangan Pengelolaan Dana Desa melalui Program Jaksa Jaga Desa di Pekon Penggawa V Ilir Kecamatan Way Krui Kabupaten Pesisir Barat - Heni Nabila (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The Village Head's supervision of village fund management is not yet optimal, resulting in legal implications for the increased risk of administrative violations and mismanagement of village funds. This study aims to analyze the Village Head's supervision in preventing mismanagement of village funds through the Village Attorney Guard Program from the perspective of Siyasah Tanfidziyyah. This study used a field research method with a qualitative approach through interviews, observation and documentation. The results show that the Village Attorney Guard Program strengthens preventive supervision through legal assistance and guidance for village officials. This research contributes to enriching the study of Siyasah Tanfidziyyah and serves as a reference in strengthening the oversight of accountable village fund management.